Various skills together - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The International Centre for development oriented Research in Agriculture (ICRA) is organising a training course to enhance interdisciplinary team work skills for participatory rural development. The English course will be from 13 January to 24...